ROSS-SECTOR COLLABORATION IN THE CONTROL OF MALARIA IN MENOREH HILL KULON PROGO REGENCY - Lesmana, Tedy Candra (Jurnal Kesehatan Masyarakat, 2013)
ABSTRACTBackground. One of the policies Health Agency (HA) Kulon Progo Regency to control malaria with cross-sector collaboration involving other governmentagencies, particularly the environmental control activities. HA has beenconducting advocacy and outreach across sectors malaria control to anotheragencies, but has not fully get their response.